2016
DOI: 10.1002/oby.21435
|View full text |Cite
|
Sign up to set email alerts
|

CNV analysis and mutation screening indicate an important role for the NPY4R gene in human obesity

Abstract: Objective: Genome-wide copy number variation (CNV) analyses have associated the 10q11.22 CNV with obesity. As the NPY4R gene is the most interesting candidate gene in this region, it was hypothesized that both genetic and structural variation in NPY4R might be implicated in the pathogenesis of obesity. Methods: In the first part of this study, 326 children and adolescents with obesity and 298 healthy lean individuals were screened for CNV in the NPY4R-containing chr.10q11.22 region. In the second part of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
(44 reference statements)
1
23
0
Order By: Relevance
“…The first study of CNV in this region and association with BMI reported an inverse correlation: a higher gene copy number was associated with reduced BMI in an elderly Chinese cohort [ 5 ]. A similar correlation was subsequently confirmed in a German cohort [ 6 ] and a Belgian cohort of children and adolescents with obesity and healthy adults with normal weight [ 12 ]. However, in a study of young Chinese individuals no CNV was detected in the 10q11.22 region [ 13 ].…”
Section: Introductionsupporting
confidence: 66%
“…The first study of CNV in this region and association with BMI reported an inverse correlation: a higher gene copy number was associated with reduced BMI in an elderly Chinese cohort [ 5 ]. A similar correlation was subsequently confirmed in a German cohort [ 6 ] and a Belgian cohort of children and adolescents with obesity and healthy adults with normal weight [ 12 ]. However, in a study of young Chinese individuals no CNV was detected in the 10q11.22 region [ 13 ].…”
Section: Introductionsupporting
confidence: 66%
“…NPY4R is expressed in peripheral organs including the gastrointestinal tract, liver, pancreas, and heart [ 24 ]. The specific NPY4R agonist, BA-129 inhibits the proliferation of pancreatic cancer cells in vitro [ 25 ], and genetic and structural variations in NPY4R have been implicated in the pathogenesis of obesity [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A GWAS for BMI in a small Chinese population also identified a region near 10q11.22 associated with BMI (160). Subsequent studies in European populations confirmed this association, demonstrating the utility of screening for CNV in non-European populations to identify novel variants implicated in obesity (161). Currently, the role of rare and common CNV in obesity remains relatively unexplored; however, it is unlikely that the CNV explain a significant portion of the missing heritability of obesity (162).…”
Section: Filling In the Gaps Of Missing Heritabilitymentioning
confidence: 99%